Sifat-Sifat Graf Pembagi Nol pada Gelanggang Polinom Kuosien (Z_p [x])/〈x^(n+1) 〉 ×(Z_q [x])/〈x^(n+1) 〉 - Dais Alifian Fatahillah; Ni Wayan Switrayni (University of Mataram, 2020)
Zero-divisor graph is an undirectedgraphwhose vertices are zero-divisors of a commutative ring and edges defined as if and only if .Wicaksono (2013) gave some characteristics of graph zero-divisor in the modulary integer ring. This research aims to represent the zero-divisor elements of the polynomial kuosien ring where are prime numbers and into a graph called the zero-divisor graph The method used in this research is a deduktive method. The result shows that the zero divisor graph obtained from polynomial kuosien ring is complete bipartit graph with some characteristics related to its girth, ecccentricity, radius and diameter.